Broader border taxes: A new option for European Union budget resources - Pascal Saint-Amans (Bruegel, 2024)
There is widespread agreement on the need for new resources to fund the European Union's budget in order to meet increasing spending demands, not least repayment of debt incurred as part of the EU's post-pandemic economic recovery. In particular it is seen as desirable that the EU should have 'own' resources, or reliable ongoing revenue streams. But there is little agreement on what new own resources could consist of. Limited reform so far has led to the introduction of a levy paid by EU members depending on plastic packaging waste generated in their territory and not recycled. Meanwhile, the European Commission has proposed resources for the EU budget from emissions trading revenues, and from levies collected under the EU carbon border adjustment mechanism (CBAM). There proposals are pragmatic and move in the right direction, but do not go far enough. The debate about own resources should focus on whether the EU will be able to build genuine own resources based on common tax policies. The EU suffers from 'tax leakage' in which profits are shifted from high-tax to low-tax EU countries, and from there onto no or low-tax non-EU jurisdictions, often without the application of withholding taxes. It may not be too much of a stretch to compare this situation of tax leakage with the situation addressed by CBAM - a quasi-tax at the border. So far, an opportunity for what could be seen as a tax at the border of the internal market, aiming to protect the market from harmful competition, may have been missed. Such a tax could reflect the undertaxed profit rule agreed as part of the international deal on the corporate minimum tax. Focusing on protecting the revenues of EU members by common tax borders could offer scope for new own resources.
Keywords: 330